2015
DOI: 10.1098/rspb.2014.2963
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pre- and post-choice behaviour: rats approximate optimal strategy in a discrete-trial decision task

Abstract: We simulate two types of environments to investigate how closely rats approximate optimal foraging. Rats initiated a trial where they chose between two spouts for sucrose, which was delivered at distinct probabilities. The discrete trial procedure used allowed us to observe the relationship between choice proportions, response latencies and obtained rewards. Our results show that rats approximate the optimal strategy across a range of environments that differ in the average probability of reward as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…Asymmetrical effects of increases versus decreases of reward probabilities were also apparent in spout sampling durations. These durations can be an index of choice confidence and our previous work has found this to be a robust and sensitive measure of choice preference (Lavan et al, 2011 ; Fam et al, 2015 ). Here, we found that changes in spout sampling durations between High and Low tracked the changes in reward probabilities across the three phases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Asymmetrical effects of increases versus decreases of reward probabilities were also apparent in spout sampling durations. These durations can be an index of choice confidence and our previous work has found this to be a robust and sensitive measure of choice preference (Lavan et al, 2011 ; Fam et al, 2015 ). Here, we found that changes in spout sampling durations between High and Low tracked the changes in reward probabilities across the three phases.…”
Section: Discussionmentioning
confidence: 99%
“…An additional constraint was that each phase had a maximum length of five sessions in the event that rats failed to reach criteria levels of performance. The choice of five sessions was based on our previous work where we found that rats made behavioral adjustments within 5 sessions following contingency reversal (Lavan et al, 2011 ; Fam et al, 2015 ). Constraining the session length was important for ensuring that rats would not have vastly different levels of experience with phase contingencies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These behavioral correlates of choice were compared between rats and humans, in addition to comparing differences in choice allocation. Our previous work found response latencies to be informative beyond choice allocation as to how environmental contingencies shape mechanisms underlying choice 20 21 22 . Specifically, we proposed that pre-choice latencies reflected outcome (i.e.…”
mentioning
confidence: 99%